Biochemical characterization of chitin synthase activity and inhibition in the African malaria mosquito, Anopheles gambiae - Zhang, Xin; Zhu, Kun Yan (My University, 2013)
Chitin synthase (CHS) is an important enzyme catalyzing the formation of chitin polymers in all chitin containing organisms and a potential target site for insect pest control. However, our understanding of biochemical properties of insect chitin synthases has been very limited. We here report enzymatic and inhibitory properties of chitin synthase prepared from the African malaria mosquito, Anopheles gambiae. Our study, which represents the first time to use a nonradioactive method to assay chitin synthase activity in an insect species, determined the optimal conditions for measuring the enzyme activity, including pH, temperature, and concentrations of the substrate UDP–N-acetyl-D-glucosamine (GlcNAc) and Mg[superscript ++]. The optimal pH was about 6.5-7.0, and the highest activity was detected at temperatures between 37 and 44°C. Dithithreitol is required to prevent melanization of the enzyme extract. CHS activity was enhanced at low concentration of GlcNAc, but inhibited at high concentrations. Proteolytic activation of the activity is significant both in the 500xg supernatant and the 40,000xg pellet. Our study revealed only slight in vitro inhibition of An. gambiae CHS activity by diflubenzuron and nikkomycin Z at the highest concentration (2.5 μM) examined. There was no in vitro inhibition by polyoxin D at any concentration examined. Furthermore, we did not observe any in vivo inhibition of chitin synthase activity by any of these chemicals at any concentration examined. Our results suggest that the inhibition of chitin synthesis by these chemicals is not due to direct inhibition of chitin synthase in An. gambiae.
Keywords: Anophele gambiae; Chitin synthase; Diflubenzuron; Enzyme inhibition